HISTOMOIlPlfQi^OGY OF THE TASTE RECEPTORS OF SOME FRESHWATER FISHES - Kulshreshta, S D (Indian Journal of Fisheries, 2011)
The taste receptors or buds are ovoid clusters of modified epithelial cellswhich are embedded in the:s^fttifled epithelium of various organs. They aredistinct frcmi the neuromast organs of the lateral-line system and, accordingly,Walter (1928) has named the ta$te receptors as gustoreceptors and the neuromastorgans as rheoreceptors